Plasma Level of Umbilical Cord Hemeoxygenase-1 (HO-1) and Neonatal Outcome in Early Onset and Late Onset Severe Preeclampsia - Muhammad Ilham Aldika Akbar; Indah Mayang Sari; Ernawati Ernawati; Aditiawarman Aditiawarman (Molecular and Cellular Biomedical Sciences, 2019)
Background: Many studies had discovered that early onset severe preeclampsia (EO-PE) has worst maternal and neonatal outcome compared to late-onset type (LO-PE), related to its placental involvement. Severe preeclampsia was defined as newly onset severe hypertension developed after 20 weeks gestation in previously normal blood pressure women, with coexistence of proteinuria, or maternal organ or uteroplacental dysfunction. Hemeoxygenase-1 (HO-1) is an enzyme with multiple effect which is protective to pregnancy.Materials and Methods: The total study subjects were 40 pregnant women consisted of 10 EO-PE, 10 normal early onset pregnancy (EO-NP), 10 LO-PE, and 10 normal late onset pregnancy (LO-NP). As much as 5 cc of plasma from umbilical cord was taken as soon as the baby was born, and the HO-1 level was examined by enzyme-linked immunosorbent assay (ELISA). The primary outcome were umbilical cord HO-1 level and neonatal composite morbidity (low Apgar score, low birthweight, length of stay >5 day, respiratory distress syndrome, jaundice and neonatal death).Results: The plasma level of HO-1 in EO-PE subjects were lower than EO-NP (0.96±0.37 ng/mL vs. 2.43±0.58 ng/mL, p<0.001). There were no significant differences in the level of HO-1 in LO-PE and LO-NP (2.18±1.07 ng/mL vs. 3.02±0.64 ng/mL, p=0.277). Plasma level of umbilical cord HO-1 of EO-PE patients was lower compared to LO-PE (0.96±0.37 ng/mL vs. 2.18±1.07 ng/mL, p=0.034). Neonatal outcome of EO-PE was worse than EO-NP (p=0.033), and LO-PE (p=0.003), while in LO-PE did not different with LO-NP (p=0.211).Conclusion: EO-PE is associated with lower plasma umbilical cord level of HO-1 and worse neonatal outcome compared to LO-PE. This indicating abnormal placental blood vessel development, placental ischemia in EO-PE, lead to reduced uteroplacental perfusion and significantly worse neonatal outcome compared to LO-PE.Keywords: severe preeclampsia, early onset preeclampsia, late onset preeclampsia, hemeoxygenase-1